Socioeconomic disparities in physical activity among Swedish women and trends over time - the population study of women in Gothenburg - Maria Waller; Lauren Lissner; Dominique Hange; Valter Sund; Ann Blomstrand; Cecilia Björkelund (Taylor & Francis Group, 2018)
Objective: To explore secular trends in physical activity in relation to socioeconomic position in middle-aged women, with focus on whether the social gaps have become wider, narrower, or remain unchanged. Design: Cohort comparisons between two representative samples of women, recruited in 1980-81 and 2004-05 as a part of the Population Study of Women in Gothenburg. Setting: Gothenburg, the second largest city of Sweden, with ≈ 450 000 inhabitants. Subjects: Population-based cohorts of 38- and 50-year-old women, invited in 1980-81 and 2004-05 to free health examinations. The study population in 1980 was n = 477, 38- and 50-year-old women born in 1930 (n = 355) and 1942 (n = 122), and in 2004 n = 500, 38- and 50-year- old women born in 1966 (n = 207) and 1954 (n = 293). Main outcome measure: Physical activity at work and leisure time. Socioeconomic position was defined based on socio-occupational group and level of education. Physical activity during work and leisure time was based on questionnaires. Results: On average 38- and 50-year-old women were more physically active at work and leisure time in 2004-05 compared to 1980-81; odds ratio (OR) for increase over time for physical activity at work for 38-year-olds: 2.59, (95% confidence interval (CI) 1.65-4.07), and for 50-year-olds: OR 2.09 (1.52-2.88); OR for increase physical activity leisure time in 38-year-olds: 1.93 (1.25-2.98), and in 50-year-olds 2.04 (1.49-2.79). There were no significant differences between socioeconomic groups in physical activity levels changes over time. Conclusion: Women in different socioeconomic groups improved their physical activity at work and leisure time to the same extent from 1980 to 2004, indicating that the socioeconomic gap in physical activity is neither increasing nor decreasing.Key Points   The gap in physical activity levels between socioeconomic groups seems to have remained stable for middle-aged women the last 25 years.   • However, women were more physically active in 2004 at work and during leisure time, independent of socioeconomic position, compared to 1980.   • It remains a great challenge to create structures that enable these behaviours for all social groups.